Osteosarcoma of head and neck: A retrospective study on prognostic factors from a single institute database. (July 2016) - Chen, YiMing; Shen, Qingcheng; Gokavarapu, Sandhya; Lin, Chengzhong; Yahiya,; Cao, Wei; Chauhan, Shubhra; Liu, Zheqi; Ji, Tong; Tian, Zhen
Highlights: The current literature is sparse in the representation of Chinese population for HNOS. Very few retrospective studies guide treatment plan. They are atypical to other sites and need customized therapy. Summary: Background: Osteosarcoma is a common bone malignancy occurring infrequently in head and neck region, the NCDB database of osteosarcoma suggests that the survival and prognosis of the head and neck osteosarcomas lie midway among other sites of occurrence, poorest survival is pelvic region and best is upper extremity. The influence of other prognostic factors independently effecting survival and recurrence are not studied widely because of scarce data even in databases. More over; these database are underrepresent eastern population. The authors institute treated around 160 head and neck osteosarcomas (HNOS) from 2007 to 2013 which were evaluated retrospectively for prognostic factors effecting survival and recurrence in specific population. Patients and method: The historical records of patients treated for head and neck osteosarcomas from 2007 to 2013 were charted. The clinical and pathological factors affecting the local recurrence (LR), overall survival (OS), disease free survival (DFS), metastasis (MT) were analyzed in univariate and multivariate cox regression model for survival. Results: A total of 160 HNOS patients were treated in the given time period, and 137 patients with follow up were analyzed. The median period of follow up was 3.067 ± 0.356 years for the alive patients. In the multivariate cox regression model for OS; surgical margin ( p  = 0.000) was most significant, histological grade was borderline ( p  = 0.062). For LR: surgical margin ( p  = 0.002), histological subtype ( p  = 0.048) and histological grade ( p  = 0.024). For MT; surgical margin ( p  = 0.000) was the significant factor. Conclusion: Histological grade and unclear margins are the significant independent prognostic factors effecting disease outcome of HNOS.